EVALUASI PENERAPAN METODE DESIGN AND BUILD PADA PROYEK PEMBANGUNAN STADION KABUPATEN KEDIRI - Wiwik Nurdianti (SONDIR, 2025)
The selection of the right procurement method is expected to achieve the success of a project, namely achieving the objectives of the project itself. Procurement or procurement of goods / services with the Design and Build method is new in Kediri Regency, this method has just been applied for the first time, namely in the Kediri Regency Stadium Development Project. This study aims to determine the obstacles experienced in the application of the Design and Build Method and determine improvements that can be made to improve the performance of the next Design and Build project implementation. The research method is descriptive quantitative. Data was collected from field data and questionnaires involving 27 respondents from the Owner, Contractor, Construction Management Consultant and Evaluation Team. The results of the questionnaire were then analyzed using mean calculations and Focus Group Discussions. The results of this study are obstacles in the implementation of the Design and Build Method on the Kediri Regency Stadium Development project, namely: from the aspect of regulation / regulation, aspects of client capability / ability, aspects of capability / ability of other stakeholders, aspects of adaptation. Improvements that can be made to the implementation of the Design and Build Method, namely: Each stakeholder must understand in detail the concept of the Design and Build Method in accordance with the rules. The details of the rules are more clarified so that the implementation of the design and build project does not cause different perceptions between stakeholders. Design and Build work requires careful planning and good collaboration from various parties.